2015
DOI: 10.1021/jacs.5b07427
|View full text |Cite
|
Sign up to set email alerts
|

Entropic Contribution of Elongation Factor P to Proline Positioning at the Catalytic Center of the Ribosome

Abstract: The peptide bond formation with the amino acid proline (Pro) on the ribosome is slow, resulting in translational stalling when several Pro have to be incorporated into the peptide. Stalling at poly-Pro motifs is alleviated by the elongation factor P (EF-P). Here we investigate why Pro is a poor substrate and how EF-P catalyzes the reaction. Linear free energy relationships of the reaction on the ribosome and in solution using 12 different Pro analogues suggest that the positioning of Pro-tRNA in the peptidyl t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
109
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 64 publications
6
109
1
Order By: Relevance
“…Our results are in line with previous studies which have described that most of these amino acids act badly during peptide bond formation, e.g. presence of a secondary amino group in proline has been associated with slow peptide bond formation and translation (16,27). Previous studies have also detected poor reactivity for glycine and for basic amino acids arginine and lysine (4,58).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in line with previous studies which have described that most of these amino acids act badly during peptide bond formation, e.g. presence of a secondary amino group in proline has been associated with slow peptide bond formation and translation (16,27). Previous studies have also detected poor reactivity for glycine and for basic amino acids arginine and lysine (4,58).…”
Section: Discussionsupporting
confidence: 93%
“…Our in vivo study cannot rule out that the observed ribosome stalls could be provoked by the down regulation of other translation elongation factors. However, the direct binding of eIF5A to the 80S ribosome, and a role in peptide bond formation demonstrated by previous crystallography and biochemical studies (9,2427), suggest that the effects we describe herein are also direct. The frequency of specific amino acids at the P- and A-sites in the eIF5A-regulated motifs suggests that eIF5A facilitates the formation of peptide bonds in situations of slow reactivity when glycine, proline, or an acidic amino acid, acts as a donor and when proline, glycine or a basic amino acid acts as an acceptor (Figure 6C).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…1416 When EF-P is bound to the ribosome the rhamnosylated arginine protrudes towards the peptidyltransferase center thereby contributing to the favorable positioning of the peptidyl-Pro-tRNA and stabilization of the CCA-end of the prolyl-tRNA. 14,17,18 Loss of the rhamnose modification abolishes the pathogenicity of P. aeruginosa 14 and increases its susceptibility to certain antibiotics. 15 Thus inhibition of EF-P rhamnosylation might be a novel strategy to selectively suppress virulence.…”
Section: Introductionmentioning
confidence: 99%
“…remedies proline-induced pausing by binding to the ribosome near the pepitdyl transfer site and makes synthesis of oligoprolines entropically favorable (5). The presence of EF-P alone is not sufficient to maintain efficient translation of oligoprolines because the active protein also requires posttranslational modification (6 -9).…”
mentioning
confidence: 99%